Market Failures as A Justification for State Aid in the European Union - Piotr PODSIADŁO (Communications of International Proceedings, 2025)
From the perspective of economic thought on State interventionism, it is important to note that State aid may be justified primarily on the grounds of social welfare if the free market mechanism does not produce satisfactory results. In such a case, the judicious implementation of State intervention can facilitate the optimisation of production factor allocation, mitigate market inefficiencies, and enable the attainment of objectives that are aligned with the collective interest. The objective of this article is to present the evolution of perspectives within economic theory on the rationale for State intervention in market mechanisms in instances of market failures. The author posits that market failures imply the non-fulfilment of the assumptions underlying the model of perfect competition, thereby hindering the attainment of both overall equilibrium and maximum total welfare. This suggests that the absence of optimal market efficiency in the Pareto sense may provide a rationale for State interventionism aimed at ensuring the optimal allocation of resources. Consequently, market inefficiencies provide a rationale for State intervention and legitimise public authorities in implementing specific legal, administrative and economic regulations within the context of enterprise aid. It is imperative to ensure that the magnitude of aid granted is judiciously balanced to mitigate potential adverse consequences that could exacerbate market disruptions.
Keywords: European Union; State aid policy; Market failures; Institutional economics; Mainstream economic paradigms